2022
DOI: 10.3390/app12031177
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Xylem Vessel Size on Grapevine Cultivars and Relationship with Incidence of Esca Disease, a Threat to Grape Quality

Abstract: Esca disease is one of the most important grapevine trunk diseases. It seriously reduces the quality and quantity of grapevine production, and results in a shorter vineyard lifespan. Previous studies have suggested that wide xylem vessel diameter favours development on grapevine of Phaeomoniella chlamydospora, one of the fungi involved in esca, thus affecting disease susceptibility. In this study, cultivars mainly originated from European countries, 27 white-berried and 24 red-berried grapevine cultivars, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…In accordance with previous results, Sauvignon Blanc and Cabernet Sauvignon showed the highest DI in the surveyed Hungarian germplasm collections, all four with their own climate and soil characteristics, while Furmint, Chardonnay and Cabernet Franc were found less GTD susceptible [12,42,43,46,55]. Blaufraenkisch (also referred to as Limberger), again confirmed by our current results, constistently one of the lowest DI [42,43,46,55], while Merlot and Pinot Noir usually were also found less susceptible to most of GTDs in general [12,42,46,55,56].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with previous results, Sauvignon Blanc and Cabernet Sauvignon showed the highest DI in the surveyed Hungarian germplasm collections, all four with their own climate and soil characteristics, while Furmint, Chardonnay and Cabernet Franc were found less GTD susceptible [12,42,43,46,55]. Blaufraenkisch (also referred to as Limberger), again confirmed by our current results, constistently one of the lowest DI [42,43,46,55], while Merlot and Pinot Noir usually were also found less susceptible to most of GTDs in general [12,42,46,55,56].…”
Section: Discussionsupporting
confidence: 91%
“…Comparing the sensitivity of different grapevine cultivars to esca, significant differences were found between those with red and those with white berries, and their respective xylem vessel diameter and density [46]. The average vessel diameter of the white cultivars was larger with higher densities, compared to the red grapevines.…”
Section: Discussionmentioning
confidence: 90%
“…The implications of the differences in the connection between the rootstock and scion hardwood cuttings apparently fade as the vine age, however, it is necessary to keep in mind that it could have other negative consequences on the future development of the vines. Misalignment results in an increase of necrotic wood tissue at the graft junction (Milien et al 2012) that could favour the development of wood fungi inside the vine (Gambetta et al 2009, Foglia et al 2022) and might have a negative effect on vineyard performance in the mid-term and even reduce its longevity.…”
Section: Grapevine Growthmentioning
confidence: 99%
“…Furthermore, it has been shown that some cultivars, e.g., ‘Cabernet Sauvignon’, ‘Grechetto’ or ‘Sangiovese’, are more susceptible to GLSD than others, e.g., ‘Chardonnay’, ‘Pinot’ or ‘Merlot’ [ 39 , 40 , 41 , 42 ]. This cultivar-dependent susceptibility probably correlates with the number and the width of xylem vessels; cultivars with larger vessels are considered to be more vulnerable to drought-stress-induced xylem cavitation and embolism [ 4 , 6 , 43 , 44 , 45 , 46 ]. In this context, drought-stress or, in general, climate conditions have also been reported to contribute to symptom expression [ 34 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%